IMPLEMENTASI APLIKASI PENCATATAN KEUANGAN PRIBADI BERBASIS ANDROID - Akhmad Budi (Jurnal Informatika dan Bisnis, 2016)
As more rapidly development of technology today, affecting the development of the smartphone operating system. The purpose of making this smartphone is to help, lighten, accelerate and simplify the lives of humans in performing daily activities. One of the smartphone operating system being developed in the community is Android. Therefore, it would be very helpful if we had a program to include the activities of the financial system - transactions/cash flow. To design a personal finance application, the author uses the theories from a variety of sources, the theories is have been used an information system, finance, smartphone, UML, Android, Eclipse, Java, PHP, XML, SQLite. Applications are develop is the Android-based applications with the Java programming language and XML. In this research, the data collected is done by doing and the application system described by object-oriented analysis and described using the Unified Modeling Language (UML). The results from this research is personal finance application that can be used by all people, especially for anyone who wants to record the financial electronically without using paper/note/book or anyone who frequently forget to arrange finances so that this application is useful as a reminder of the cash flow. With features such as data import, export data and share data. User need not worry about lost data because the data on this application can be backed up even shared to email or etc. The conclusion of this research that the personal finance application has been based on Android, so it can be used on Android mobile devices. Data from this application is already stored in the database so it is more easily processed by the application and displayed to the user in the form of reports that organized and neat. So users of this application is not difficult to use.Keywords: Android, system information, financial records, technology